2000
DOI: 10.2514/3.14579
|View full text |Cite
|
Sign up to set email alerts
|

Nonlinear response of composite panels under combined acoustic excitation and aerodynamic pressure

Abstract: J/j_aA finite element formulation is presented for the analysis of large deflection response of composite panels subjected to aerodynamic pressure at supersonic flow and high acoustic excitation. The first-order shear deformation theory is considered for laminated composite plates, and the von Karman nonlinear straindisplacement relations are employed for the analysis of large deflection panel response. The first-order piston theory aerodynamics and the simulated Gaussian white noise are employed for the aerod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0
1

Year Published

2007
2007
2020
2020

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 0 publications
0
5
0
1
Order By: Relevance
“…(11) will not bring significant error, because their natural frequencies are usually two to three orders of magnitude higher than those of bending [16].…”
Section: B Constitutive Equationsmentioning
confidence: 98%
See 1 more Smart Citation
“…(11) will not bring significant error, because their natural frequencies are usually two to three orders of magnitude higher than those of bending [16].…”
Section: B Constitutive Equationsmentioning
confidence: 98%
“…Locke [15] investigated the large deflection random vibration of a thermally buckled thin isotropic plate using the method of equivalent linearization and assuming temperature-independent material properties. Abdel-Motagaly et al [16] adopted finite element numerical integration to study the nonlinear panel response of thick composite-plate panels under combined aerodynamic and acoustic loads. Dhainaut et al [17,18] presented a finite element solution for the prediction of nonlinear random response of thin isotropic and composite panels subjected to the simultaneous action of band-limited white-Gaussian noise and elevated temperatures.…”
Section: Introductionmentioning
confidence: 99%
“…In the present study, mode shapes, which satisfy the boundary conditions shown in Eq. (14), are assumed to be…”
Section: Aerodynamic Modelingmentioning
confidence: 99%
“…Motagaly et al [14] gave the response of nonlinear panels subjected to combined acoustic and aerodynamic pressures using finite element method. The simulation indicated that the acoustic pressure should be considered for λ > λ cr .…”
Section: Introductionmentioning
confidence: 99%
“…Locke [10] investigated the large deflection random vibration of a thermally buckled thin isotropic plate, using the method of equivalent linearization, while assuming a temperature-independent material properties. Abdel-Motagaly et al [11] used finite element numerical integration to study nonlinear panel response under combined aerodynamic and acoustic loads. Dhainaut et al [12] and [13] presented a finite element formulation for the prediction Shape memory alloys (SMAs) have a unique ability to completely recover large prestrains (up to 10%) when heated above certain characteristic temperature called the austenite finish temperature.…”
Section: Introductionmentioning
confidence: 99%